Teaching visual thinking in radiology. - Macura, R. T. (American Medical Informatics Association, 1994)
We have implemented a tutoring system, Radiology Puzzler, for teaching visual recognition of intracranial lesions on radiological images. The system is designed to support the learning of radiological patterns through graphical case retrieval. Using radiologic feature samplers, the user may define brain lesion characteristics and use visual query when searching for reference cases. A rule-based module generates a hierarchical list of diagnostic hypotheses and provides a feed-back to the user. Relevant cases that match the sampler's index are retrieved from the case library for comparison with the case in question.